Financial Feasibility Analysis and Business Sensitivity Level on Intensive Aquaculture of Vaname Shrimp (Litopenaeus Vannamei) - Abdul Muqsith; Heri Ariadi; Abdul Wafi (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
Intensive aquaculture of vaname shrimp (L. vannamei), has been known to be a favorite for aquaculture commodities in Indonesia at the last 2 decades. The purpose of this study was to determine status of financial feasibility and business sensitivity rate in intensive shrimp culture activities. The research method used in this study is a quantitative method. The data analysis used to determine of financial feasibility and business sensitivity in the form of NPV analysis, Net B/C, R/C, IRR, and payback period. Also, an analysis of assumptions about rising feed prices and decreasing production revenues for the level of business sensitivity. The results showed that the shrimp culture business was categorized as feasible and profitable with NPV value of IDR 63,417,262,006, Net B/C 29.11, R/C 2.14, IRR 42.46%, and PP 1.4 years. Sensitivity analysis shows that the business is not so sensitive to the increase of feed prices and decreased revenue, but is very sensitive if both conditions change simultaneously, but are still in the financially feasible category. So, it can be concluded based on NPV, Net B/C, R/C, IRR, and payback period indicator analysis that intensive white shrimp farming is very feasible and profitable to use with a low level of business sensitivity due to feed price fluctuations changes and uncertain operational business revenues.